Electroconvulsive Therapy Use in Pregnant Patients Case Report - Roxana Nouri-Nikbakht,; Levitt, Dr. Gwen (International Journal of Medical Students, 2023)
Background: ECT has been used as an intervention for patients with treatment resistant depression, sever psychosis, catatonia, acute mania, certain types of schizophrenic syndromes, and suicidality. ECT is safe in all trimesters, whereas certain medications are only safe at certain times during pregnancy and can be associated with more severe side effects. ECT does not interfere with breastfeeding. Moreover, ECT use in pregnancy has not been shown to increase risk of labor and delivery complications or congenital anomalies, while untreated depression or pharmacotherapy for depression can do so. Case Presentation: We discuss three cases in which pregnant patients with psychiatric diagnoses of bipolar disorder or schizoaffective disorder receive ECT in combination with pharmacotherapy. ECT improved the symptoms of the patients in these cases, but only one of the three patients was discharged home with her baby. Conclusion: The women in these cases demonstrate that ECT can be a helpful treatment for psychosis and depression, especially in combination with pharmacotherapy. ECT is safe and effective for both the mother and the fetus. ECT should be considered alongside other mainstays of treatment with special consideration to possible pregnancy-related safety measures.